Development of short- and continuous carbon fiber-reinforced ZrB2-SiC-ZrC matrix composites for thermal protection systems. Issue 13 (September 2018) - Inoue, Ryo; Arai, Yuraro; Kubota, Yuki; Goto, Ken; Kogo, Yasuo
Abstract: Short and plain-woven continuous carbon fiber-reinforced ZrB2 -SiC-ZrC (Csf /ZSZ and Cpw /ZSZ) matrix composites were fabricated by a Si melt-infiltration process for application to thermal protection systems (TPSs). The fracture toughness of both composites was improved compared to those of ZSZ ceramics. The effects of the thermal properties, volume fraction, and architecture of the carbon fibers on the oxidation behaviors of the composites were also examined by oxyhydrogen torch testing. The experimental results showed that the oxidation of both composites significantly depended on the microstructural parameters and properties of the constituent materials. In particular, the high thermal conductivity of the Csf /ZSZ composite was important in preventing local increases in temperature and material consumption. In the present study, the starting material, volume fraction, and architecture of carbon fibers were identified as important parameters for the development of TPS materials.